The activities of the Taklim Council during the Covid-19 Pandemic at the Al Ittihad Gadut Mosque Kecamatan Pauh Kota Padang - Mayu Nepradeni; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by the implementation of majelis taklim activities during the Covid-19 pandemic by following health protocols. This study aims to determine the description of the planning, know the description of the implementation, and know the description of the existing supervision in the activities of the Taklim Assembly during the Covid-19 pandemic. This research is a quantitative descriptive study with an ex post facto approach. The subjects of this study were members / jama'ah of the Al Ittihad Al Ittihad Assembly Activities in Pauh Subdistrict, Padang City. The population was 44 people and a sample of 3 administrators and 30 members / jama'ah were taken from 70% of the total population using the Simple Ramdom Sampling technique. Data collection tools in this study using a questionnaire. The data analysis technique used in this study was to use the percentage formula. The results showed that the activities of majelis taklim during the Covid-19 pandemic were categorized as good in terms of planning, implementation, monitoring aspects. Suggestions from this research are expected that majelis taklim activities will continue to run well and be further improved in planning, implementing, and supervising activities.Keywords: activities, assemblies, taklim